6(2x+1)=3(x+8)

Simple and best practice solution for 6(2x+1)=3(x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x+1)=3(x+8) equation:



6(2x+1)=3(x+8)
We move all terms to the left:
6(2x+1)-(3(x+8))=0
We multiply parentheses
12x-(3(x+8))+6=0
We calculate terms in parentheses: -(3(x+8)), so:
3(x+8)
We multiply parentheses
3x+24
Back to the equation:
-(3x+24)
We get rid of parentheses
12x-3x-24+6=0
We add all the numbers together, and all the variables
9x-18=0
We move all terms containing x to the left, all other terms to the right
9x=18
x=18/9
x=2

See similar equations:

| 3(2x-1)=0.5(x+6) | | 4x+5=11+3x | | 5x–18=7 | | 8x^2+8x=424 | | 11m=8m-6 | | -45x-20=20x-12 | | 14x+6-5x=34+5x+19 | | x*5-24=31 | | 10(3.14)*360/10(3.14)=x | | 9/11=x/661 | | -2y-4=2 | | 6(x-3)-2-(x+4)=2 | | 2x+3x-14+(x+5)=39 | | -2(4+2x)=4x | | m/9+3=7 | | 12r=5r+7 | | 2(x+5)-12=5+x | | -5x+3=-2x+5-3x | | 36=g2 | | 15x+-15=180 | | t2=200 | | a/4+8=10a= | | 44-2m=38 | | 19+5.5h=10+6.75h | | 3(5-n)=-7 | | -9-x/3=4 | | C(×)=0.5x^2-280x+52,506 | | 3n+7–n=25 | | 3(v+5)=-3v-45 | | -88=8m | | 35=1/2⋅g⋅5 | | 60+-4x=180 |

Equations solver categories